Simultaneous qualitative and quantitative determination of compounds in Aloe arborescens Mill using liquid chromatography with ion trap time‐of‐flight mass spectrometry and diode array detectors. Issue 10 (19th June 2018) - Li, Tiantian; Liao, Ziqiong; Chen, Mingyi; Liu, Deliang; Zhang, Shaobao; Lin, Lei; Zheng, Haihui; Liao, Qiongfeng; Xie, Zhiyong; Song, Fenyun
Abstract: An effective and comprehensive method was developed for the simultaneous analysis of compounds in the powder of Aloe arborescens Mill by liquid chromatography with ion trap time‐of‐flight mass spectrometry and high‐performance liquid chromatography with diode array detection. Qualitative analysis of all the compounds presented in Aloe arborescens Mill was performed by liquid chromatography with ion trap time‐of‐flight mass spectrometry. A total of 28 components from Aloe arborescens Mill were identified, including chromones, phenyl pyrones, anthrones and anthraquinones. The quantitative analysis of multi‐components by a single‐marker method was developed and validated for the simultaneous determination of aloenin, 2′‐α‐rhamnopyranosylisovitexin, aloinA, and aloinB in Aloe arborescens Mill leaves using high‐performance liquid chromatography. We can than calculate the contents of the other constituents with the relative correction factors correspondingly. In comparison with the results obtained using the external standard method, the quantitative analysis of multi‐components by the single‐marker method demonstrates no significant difference. This is the first simultaneous characterization and quantitative determination of multiple compounds in Aloe arborescens Mill. It can be applied to standardize the quality of Aloe arborescens Mill as well as the future design of nutraceutical and cosmetic preparations.